Demystifying the controversies and outcome : toric intraocular lens implantation in cataract patients with corneal astigmatism post pterygium surgery - Ahmad Fauzi, Nadhirah; Akhtar Ali, Ahmad Nurfahmi; Abdul Razak, Zulhilmi; Mohd. Kamal, Khairidzan (2019)
Purpose To evaluate the accuracy of toric intraocular lens (IOL) implantation in cataract patients with corneal astigmatism post pterygium surgery. Methods In this prospective case series, six patients who had corneal astigmatism post pterygium surgery were implanted with Zeiss toric IOL (AT-TORBI 709). Preoperative corneal regularity and symmetry pattern was measured with placido disc topography (Zeiss Atlas 900) examination. Three-month postoperative corneal astigmatism was measured with Zeiss IOLMaster 700 and compared with the manifest astigmatic refractive outcome in patients implanted with toric IOLs. The postoperative refractive astigmatism prediction error was calculated by vector analysis derived from Barrett toric calculator to predict the required toric IOL cylinder power. Results The spherical equivalent recorded for the postoperative refraction is +0.50 ± 1.00D with logMAR of 0.0 to 0.05. The mean for preoperative corneal astigmatism and postoperative refractive astigmatism are 1.45 ± 0.87D and 0.38 ± 0.19D respectively (P 0.001). The mean absolute error in predicted residual astigmatism is 0.37 ± 0.16D and with-the-rule centroid error of 0.26 ± 0.34D @ 26. The postoperative refractive astigmatism resulted with 33.0% achieved less than -0.25D, 67.0% obtained less than -0.50D and 100.0% of eyes were within -0.25D to -0.75D. Conclusion Toric IOL provides low post operative astigmatism correction and better predictive error in patients with post pterygium excision